Barriers Faced by American Indian Women in Urban Wisconsin in Seeking Help Following an Experience of Intimate Partner Violence - Luebke, Jeneile (Violence against women, 2023)
American Indian1 (AI) women experience high rates of intimate partner violence (IPV) and face many barriers when help-seeking. This study aims to understand better the context of IPV and help-seeking behaviors for urban AI women after experiences with IPV. Postcolonial and Indigenous feminist frameworks framed this critical ethnography study. Semistructured interviews with 34 AI IPV survivors2 living in Wisconsin urban areas were conducted. Our findings highlight context-specific structural barriers to help-seeking after experiences of IPV heightened by the COVID-19 pandemic. Context-specific and survivor-led interventions are necessary to address and reduce barriers that urban AI women face.